Depositional record of trace metals and degree of contamination in core sediments from the Mandovi estuarine mangrove ecosystem, west coast of India. Issue 1 (15th February 2015) - Veerasingam, S.; Vethamony, P.; Mani Murali, R.; Fernandes, B.
Highlights: Depositional trends of trace metals in Mandovi estuary were established. Lithogenic and anthropogenic sources of metals were studied using SEM. Degree of pollution is assessed using geo-accumulation index of trace metals. Fe and Mn are highly enriched in the Mandovi estuary than other Indian estuaries. Abstract: The concentrations of seven trace metals (Fe, Mn, Cu, Cr, Co, Pb and Zn) in three sediment cores were analysed to assess the depositional trends of metals and their contamination level in the Mandovi estuary, west coast of India. All sediment cores showed enrichment of trace metals in the upper part of core sediments and decrease in concentration with depth, suggesting excess of anthropogenic loading (including mining activities) occurred during the recent past. Scanning electron microscope (SEM) images distinguished the shape, size and structure of particles derived from lithogenic and anthropogenic sources in core sediments. The geo-accumulation index ( I geo ) values indicate that Mandovi estuary is 'moderately polluted' with Pb, whereas 'unpolluted to moderately polluted' with Fe, Mn, Cu, Cr, Co and Zn. The comparative analysis of trace metals revealed that Fe and Mn were highly enriched in the Mandovi estuary compared to all other Indian estuaries.